Substantive Legal Justice Regarding the Judge's Legal Considerations Towards Perpetrators of the Criminal Acts of Narcotics Distribution - Gina Salsabila Putri; Sanusi; Muhamad Noupel (Journal of Social Research, 2026)
Narcotics crimes are complex crimes that raise issues in determining criminal liability, particularly for intermediaries. This study aims to analyze the judge's legal considerations in Decisions Number 79/Pid.Sus/2025/PN Cbn and Decision Number 761/Pid.Sus/2025/PN Bdg and examine the forms of criminal liability for narcotics distributors. The research method used was normative legal research with a statutory, conceptual, and case approach. The data used are primary and secondary legal materials analyzed qualitatively. The results show that the judge's considerations are not only based on the fulfillment of the elements of the offense, but also on the defendant's role in the network, the level of culpability, and the subjective condition of the perpetrator. In the Cirebon District Court Decision, the defendant is considered an active perpetrator and therefore is given a stricter sentence, while in the Bandung District Court Decision, the defendant is considered a subordinate intermediary and therefore is given a relatively lighter sentence despite greater evidence. Criminal liability in narcotics cases requires the fulfillment of the elements of the criminal act, the ability to be responsible, and fault. This study also found sentencing disparities due to differences in judges' assessments of the perpetrator's role.